2017
DOI: 10.1038/nmat4896
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ti3AuC2, Ti3Au2C2 and Ti3IrC2 by noble metal substitution reaction in Ti3SiC2 for high-temperature-stable Ohmic contacts to SiC

Abstract: they were stored in room-air after the annealing procedure and prior to the SEM/EDX study. 100The Si content of the A layers in the novel structure is negligible, based on EDX results, and and what is present in similar systems, see S3 and S6. These calculations showed that 115

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
126
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(139 citation statements)
references
References 36 publications
9
126
1
3
Order By: Relevance
“…19 Recently, several new MAX phase and related nanolaminated carbides have been reported, such as Ti 3 AuC 2 , Ti 3 Au 2 C 2 , Mo 2 AuC, and Mo 2 Au 2 C, synthesized by solid state reaction between the Au capping layers and the underlying nanolaminated carbide thin films (e.g., Ti 3 SiC 2 and Mo 2 Ga 2 C) at elevated temperature. [23][24][25] After the annealing, the interplanar spacing of the carbides expanded along the c-axis (denoted as out-of-plane direction in the following discussion). Substitution of Si, Al, and Ga by Au was observed using scanning transmission electron microscopy (STEM), where the chemical analysis showed the possibility of both partial substitution and full substitution.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Recently, several new MAX phase and related nanolaminated carbides have been reported, such as Ti 3 AuC 2 , Ti 3 Au 2 C 2 , Mo 2 AuC, and Mo 2 Au 2 C, synthesized by solid state reaction between the Au capping layers and the underlying nanolaminated carbide thin films (e.g., Ti 3 SiC 2 and Mo 2 Ga 2 C) at elevated temperature. [23][24][25] After the annealing, the interplanar spacing of the carbides expanded along the c-axis (denoted as out-of-plane direction in the following discussion). Substitution of Si, Al, and Ga by Au was observed using scanning transmission electron microscopy (STEM), where the chemical analysis showed the possibility of both partial substitution and full substitution.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%
“…Substitution of Si, Al, and Ga by Au was observed using scanning transmission electron microscopy (STEM), where the chemical analysis showed the possibility of both partial substitution and full substitution. [23][24][25] Along with the discovery of a new A element and additional members of the MAX phase family, it was also shown that the Ti 3 Au 2 C 2 phase can further react with an Ir capping layer, forming yet another nanolaminated phase, Ti 3 IrC 2 . This points towards a fully reversible intercalation of Au in the MAX phase, with Au diffusing in and out of the A layer without any substantial change of the metal carbide, e.g., Ti 3 C 2 , layers.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%
See 1 more Smart Citation
“…Ti3AuC2 and Ti3Au2C2, synthesized by thermally induced exchange reaction of Au into the Si layers of Ti3SiC2 thin films [53]. The authors reported that the Au-containing phases retained the nanolaminated structures and served as a high-temperature-stable Ohmic electrical contact with the underlying SiC substrate [53].…”
Section: Most Recently Fashandi Et Al Have Reported On New Max Andmentioning
confidence: 99%
“…The authors reported that the Au-containing phases retained the nanolaminated structures and served as a high-temperature-stable Ohmic electrical contact with the underlying SiC substrate [53].…”
Section: Most Recently Fashandi Et Al Have Reported On New Max Andmentioning
confidence: 99%